2011
DOI: 10.1016/j.nimb.2010.11.096
|View full text |Cite
|
Sign up to set email alerts
|

The role of projectile interactions in triply differential cross sections for excitation–ionization of helium

Abstract: We report triply differential cross section (TDCS) for the simultaneous excitation-ionization of helium by electron impact for both coplanar and non-coplanar geometry. In the coplanar case, calculations have been performed for an incident energy of 500 eV and low ejection energies (3 eV and 10 eV), whereas in the noncoplanar case we have considered impact energies in the range 1240-4260 eV for a symmetric geometry. The present calculation is based on the eikonal approximation due to Glauber. We have incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They have pointed out that the eikonal approximation is superior to the FBA in the present physical process. It is worth stressing that the EA has been found to be successful in a wide variety of collisions [31][32][33][34][35][36][37] than that obtained in the FBA and classical-simulation 16 methods with the screened Rogers potential in a wide range of mean kinetic energy for Xe 6þ and Xe 10þ ions.…”
Section: Introductionmentioning
confidence: 97%
“…They have pointed out that the eikonal approximation is superior to the FBA in the present physical process. It is worth stressing that the EA has been found to be successful in a wide variety of collisions [31][32][33][34][35][36][37] than that obtained in the FBA and classical-simulation 16 methods with the screened Rogers potential in a wide range of mean kinetic energy for Xe 6þ and Xe 10þ ions.…”
Section: Introductionmentioning
confidence: 97%
“…The GA has been successfully applied to a wide variety of atomic collisions [33][34][35][36][37][38]. Recently, Dey and Roy [38] applied the GA to study the role of projectile interactions in triply differential cross sections (TDCS) for excitation-ionization of helium and found that Glauber results are in reasonably good agreement with experiment for small scattering angles.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Dey and Roy [38] applied the GA to study the role of projectile interactions in triply differential cross sections (TDCS) for excitation-ionization of helium and found that Glauber results are in reasonably good agreement with experiment for small scattering angles. The BBK method is also successfully applied to the various ionization processes [31,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison is made between the predictions of EA with the corresponding results obtained in the FBA and CL methods throughout the two energy regions. It is worth stressing that the EA has been found to be successful in a wide variety of collisions [21][22][23][24][25][26][27] such as ionization, ionization-excitation etc. .…”
Section: Introductionmentioning
confidence: 99%